2002
DOI: 10.1136/sti.78.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of syphilis among factory workers in Ethiopia: effect of an intervention based on education and counselling

Abstract: Background: The prevalence and incidence of syphilis infection were examined in a cohort study of factory workers in Ethiopia. Method: Between February 1997 and March 1999, 409 men and 348 women were enrolled and followed in the cohort study. Results: The prevalence (95% CI) of past/current syphilis (positive TPPA serology) was 28.9% (25.7% to 32.3%), and factors associated with past/current syphilis were markers of risky sexual behaviours including HIV infection. In this cohort of factory workers subject to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…In selection bias, seven articles [18,20,32,[37][38][39][40] were rated "strong" because those study participants were factory workers, and more than 80% of the selected individuals agreed to participate. Six articles [19,31,[33][34][35][36] were rated "medium" because only 60-79% of the selected individuals agreed to participate. In study design, two studies [31,37] were randomized controlled trials (RCTs), so they were rated "strong", and eleven studies [18-20, 32-36, 38-40] were cohort studies, so they were rated "medium".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In selection bias, seven articles [18,20,32,[37][38][39][40] were rated "strong" because those study participants were factory workers, and more than 80% of the selected individuals agreed to participate. Six articles [19,31,[33][34][35][36] were rated "medium" because only 60-79% of the selected individuals agreed to participate. In study design, two studies [31,37] were randomized controlled trials (RCTs), so they were rated "strong", and eleven studies [18-20, 32-36, 38-40] were cohort studies, so they were rated "medium".…”
Section: Resultsmentioning
confidence: 99%
“…In study design, two studies [31,37] were randomized controlled trials (RCTs), so they were rated "strong", and eleven studies [18-20, 32-36, 38-40] were cohort studies, so they were rated "medium". In confounders, two of the thirteen studies [35,40] were rated as "strong", ve as "medium" [18,34,36,38,39] and the remaining six [19,20,[31][32][33]37] as "weak". For two RCTs [31,37], the authors did not report whether confounding factors were balanced at baseline, so they were rated "weak".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…avoiding the progression of the disease in infected people by providing early health care and psychosocial support), as it encompasses counselling before and after HIV testing. Several studies conducted in resource-limited settings have demonstrated that VCT may be effective at preventing HIV infection and other STIs in some populations, including FSWs, serodiscordant couples and pregnant women [7][8][9][10][11][12][13]. Moreover, in a predominantly heterosexual transmission context, a VCT programme targeting high-prevalence groups with high numbers of partners such as FSWs can be very efficient in reducing the spread of HIV to the general population displaying a lower prevalence [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Figures on prevalence and incidence of syphilis in several studies from sub-Saharan Africa are based on commonly used serological screening assays. [2][3][4][5][6] However, the interpretation of non-treponemal and treponemal specific serological tests in a population where syphilis and HIV are endemic, is encountered with difficulty. [7][8][9] The rapid plasma reagin (RPR) test is a non-treponemal serological test for syphilis widely used as a screening test in antenatal clinics and other health facilities in the developing world.…”
mentioning
confidence: 99%